Application Analysis of Indoor Visible Light Communication System. Issue 4 (April 2021) - Zhang, Yong; Wang, He-nan; Cheng, Zhan-xin; Han, Dong
Abstract: The technology of using light-emitting diodes as light source for visible communication is one of the hot spots in the field of optical wireless communication. This paper analyses the characteristics of visible communication technology, focuses on the key technologies needed for the realization of visible communication system in a specific room, and studies the feasibility and application prospects of indoor visible communication combined with the development status at home and abroad.